Dimension of the Boundary in Different Metrics - Klén, Riku; Suomala, Ville (MATHEMATICA SCANDINAVICA, 2013)
We consider metrics on Euclidean domains ΩR^n that are induced by continuous densities ρΩ→(0,∞) and study the Hausdorff and packing dimensions of the boundary of Ω with respect to these metrics.